2004
DOI: 10.1002/yea.1119
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Kluyveromyces lactis subtelomeric sequences including a distal element with strong purine/pyrimidine strand bias

Abstract: Telomeres are the specialized structures at the ends of eukaryotic chromosomes and are composed of short T/G-rich DNA repeats and the proteins that interact with them. Internal to telomeres are subtelomeric regions that are species-specific and often repetitive. The yeast Kluyveromyces lactis has telomeric tracts of 10-20 copies of a 25 bp repeat, but the subtelomeric regions have not previously been characterized in detail. Here we have cloned and characterized subtelomeric regions from 10 of the 12 chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…1B). The presence of a telomere signal below 0.7 kb (the size of the subtelomere DNA in the smallest EcoRI telomere fragment in our wild-type K. lactis strain [47]) indicated that a significant amount of telomeric DNA existed in extrachromosomal form. Further passaging of the M1 mutant revealed that the highly elongated telomeres were maintained without apparent change over at least 600 cell divisions (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…1B). The presence of a telomere signal below 0.7 kb (the size of the subtelomere DNA in the smallest EcoRI telomere fragment in our wild-type K. lactis strain [47]) indicated that a significant amount of telomeric DNA existed in extrachromosomal form. Further passaging of the M1 mutant revealed that the highly elongated telomeres were maintained without apparent change over at least 600 cell divisions (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…For example, S. cerevisiae (Louis and Haber 1992), Ustilago maydis (Sanchez-Alonso and Guzman 1998), Pneumocystis carinii (Keely et al 2005), Kluyveromyces lactis (Nickles and McEachern 2004), M. oryzae (Gao et al 2002;Rehmeyer et al 2006), A. nidulans (Clutterbuck and Farman 2007), Nectria hematococca (M. L. Farman, unpublished results) and Cercospora zeae maydis (L. Dunkle and M. L. Farman, unpublished results) all possess distinct subtelomere regions consisting of sequences that are found at several chromosome ends. By contrast, none of the fully assembled Neurospora chromosome ends have similarity to one another for at least 20 kb from the telomere repeat.…”
Section: Resultsmentioning
confidence: 99%
“…AT-rich sequences in the telomere-adjacent regions and their relationship to RIP: The N. crassa telomereadjacent regions are almost universally composed of highly AT-rich DNA, a feature that is common to telomere-adjacent regions of other fungi, including K. lactis (Nickles and McEachern 2004), P. carinii (Keely et al 2005), and M. oryzae (Rehmeyer et al 2006). In these organisms, however, the AT-rich sequences are part of a distinct subtelomere domain that is duplicated at multiple chromosome ends.…”
Section: Resultsmentioning
confidence: 99%
“…As the cells used were all haploid, it is likely that the latter event also involved a shift to a new size rather than chromosome loss. Interestingly, altered chromosomes corresponded to chromosome B, the only chromosome in the 7B520 strain background that contains a telomere lacking an R element, a sequence located immediately next to telomeres with homology to all other R elements (23,61). Because the shared sequence of the R elements provides a backup means to repair deleted telomeres via homologous recombination (53), a telomere lacking an R element might be expected to be more prone to terminal deletions and rearrangements occurring as a consequence of telomere dysfunction.…”
Section: Figmentioning
confidence: 99%